2009
DOI: 10.3141/2116-09
|View full text |Cite
|
Sign up to set email alerts
|

Capacities and Deflections of Laterally Loaded Shafts behind Mechanically Stabilized Earth Wall

Abstract: Current practice for designing laterally loaded shafts that pass through a mechanically stabilized earth (MSE) wall often involves isolating the shaft from the MSE mass and anchoring the shaft into rock with a rock socket. Sizeable cost and time savings could be realized, along with continued effective performance and reliability, if a method were available to evaluate the lateral load capacity of a shaft supported by the MSE mass alone without a rock socket. The Kansas Department of Transportation assembled a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 2 publications
1
22
0
Order By: Relevance
“…The completed study by Pierson (2007) and Pierson et al (2009b) involved designing, constructing and testing drilled shafts within an MSE wall that was 43 m long and 6 m high. The wall was divided into six test sections with one wing wall at each end, as shown in Figure 1(a).…”
Section: Prototype Of the Numerical Studymentioning
confidence: 99%
See 2 more Smart Citations
“…The completed study by Pierson (2007) and Pierson et al (2009b) involved designing, constructing and testing drilled shafts within an MSE wall that was 43 m long and 6 m high. The wall was divided into six test sections with one wing wall at each end, as shown in Figure 1(a).…”
Section: Prototype Of the Numerical Studymentioning
confidence: 99%
“…4.1 Parameter determination and validation of capyield model The data from the gradation and triaxial tests along with the numerical back-analysis were utilised to determine the required Interface Properties MSE wall facing blocks Horizontal (Pierson, 2007). The shape factor, AE, was assumed to be 1 to make the compression yielding surface circular.…”
Section: Numerical Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Movement of telltales installed within the fill and attached to the geogrid, as well as targets attached to the wall facing, was monitored using a digital camera and a photogrammetric process. Additional details on construction and instrumentation are located in Pierson (2008Pierson ( , 2009.…”
Section: Construction and Instrumentationmentioning
confidence: 99%
“…Under this circumstance, the existing p-y curves are not applicable. Due to lack of information, Pierson et al [11] performed a study to assess the behavior of drilled shafts in an MSE wall and provided a threshold lateral deflection of the drilled shaft that a MSE wall can tolerate. Rollins et al [12] then studied driven pile in an MSE wall and suggested additional load to be considered in the drilled shaft and MSE wall design during a seismic event.…”
Section: Introductionmentioning
confidence: 99%